PRODUCTION OF MONOGLYCERIDES FROM CASTOR OIL USING CRUDE AND REFINED GLYCERIN. STUDY OF THE MAIN VARIABLES OF THE PROCESS - Sandra M. CARDONA V. (Universidad de Antioquia, 2010)
Monoglycerides are widely used as emulsifiers in food, pharmaceutical and cosmetic industries. In this article was reported the production of monoglycerides from castor oil, by glicerolysis reactions, using USP glycerine and crude glycerol derived from a palm-biodiesel production process. Metalic hydroxides and lead oxide were used as basic catalysts, while lead acetate was used as acid catalyst. Results showed that the lead-based catalysts exhibited higher conversions to monoglycerides respect to those based on sodium, potassium and calcium. We found that a high molar ratio oil/glycerol was a determinant variable that favors high concentrations of monoglycerides. Ultimatelly, it was shown that it is feasible to use crude glycerol for the production of monoglycerides, although in this case the concentration of monoglycerides is reduced 20% due to the poisoning of the catalysts.